Transarticular Fixation Following Mobilization of "High-Riding" Vertebral Artery. Issue 4 (15th January 2021) - Goel, Atul; Prasad, Apurva; Shah, Abhidha; Sasane, Sumeet; Hawaldar, Akshay; Biswas, Chandrima; Thomas, Antony
Abstract: BACKGROUND AND IMPORTANCE: The article identifies the feasibility of transarticular screw fixation after mobilizing the vertebral artery in cases where it is in a "high-riding" location. CLINICAL PRESENTATION: A 42-yr-old male patient had a 4-yr history of progressive quadriparesis. Investigations revealed severe basilar invagination. There was assimilation of atlas and C2-3 fusion. The vertebral artery was "high-riding" into the pedicle-facet of C2 vertebra on both sides. Vertebral artery loop was exposed and mobilized inferiorly on both sides after careful drilling of pedicular bone on the posterior aspect of the dome of the artery. C2 facetal bone on the anterior face of the vertebral artery dome was now available for screw insertion. The C1-2 facets and the articulation were directly in line, making transarticular screw fixation relatively straightforward. The wide bone space available permitted insertion of 2 screws in a transarticular fashion on both sides. The patient had satisfactory clinical improvement. Imaging after 22 mo showed bone fusion across the facets. CONCLUSION: Mobilization of the high-riding vertebral artery loop can help salvage the surgical procedure of lateral mass stabilization.